Conflict and Peacebuilding in the African Great Lakes Region - Redeker Hepner, Tricia M.; Omeje, Kenneth C. (Book collections on Project MUSE., 2013)
Driven by genocide, civil war, political instabilities, and ethnic and pastoral hostilities, the African Great Lakes Region (primarily Uganda, Rwanda, Democratic Republic of the Congo, and Burundi) has been overwhelmingly defined by conflict. An international group of scholars, including many from the Great Lakes region, turn their focus to the interlocking conflicts and efforts toward peace. These essays present a range of debates and perspectives on the history and politics of conflict, highlighting the complex internal and external sources of both persistent tension and creative peacebuilding. Taken together, the essays illustrate that no single perspective or approach can adequately capture the dynamics of conflict or offer successful strategies for sustainable peace in the region.